Evidence for an unusual transmembrane configuration of AGG3, a Class C Gγ Subunit, of Arabidopsis - Wolfenstetter, Susanne (Plant J, 2014)
Heterotrimeric G proteins are crucial for the perception of external signals and subsequent signal transduction in animal and plant cells. In both model systems, the complex is comprised of one Gα, one Gβ and one Gγ subunit. However, in addition to the canonical Gγ subunits (Class A), plants also possess two unusual, plant-specific classes of Gγ subunits (Classes B and C) not yet found in animals. These include Gγ subunits lacking the C-terminal CaaX motif (Class B) which is important for membrane anchoring of the protein, and thus give rise to a flexible subpopulation of Gβ/γ heterodimers that is not necessarily restricted to the plasma membrane. Even more interesting, plants also contain Class C Gγ subunits which are twice the size of canonical Gγs, with a predicted transmembrane domain, and a large cysteine-rich, extracellular C-terminus. However, neither the presence of the transmembrane domain nor the membrane topology has been unequivocally demonstrated. Here, we provide compelling evidence that AGG3, a Class C Ggamma subunit of Arabidopsis, contains a functional transmembrane domain, which is sufficient but not essential for plasma membrane localization, and that the cysteine-rich C-terminus is extracellular.